2018
DOI: 10.1021/jacs.8b08796
|View full text |Cite
|
Sign up to set email alerts
|

Ice Nucleation on a Corrugated Surface

Abstract: Heterogeneous ice nucleation is a key process in many environmental and technical fields and is of particular importance in modeling atmospheric behavior and the Earth’s climate. Despite an improved understanding of how water binds at solid surfaces, no clear picture has emerged to describe how 3D ice grows from the first water layer, nor what makes a particular surface efficient at nucleating bulk ice. This study reports how water at a corrugated, hydrophilic/hydrophobic surface restructures from a complex 2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 59 publications
0
40
0
Order By: Relevance
“…For example, on graphene, water has previously only been visualised when subsurface, due to its dynamic nature 61,62 . Compared with other techniques, He atom scattering has the advantage of being the most delicate surface-probing technique and is sensitive to H atoms in the top layer [63][64][65][66] . All measurements have therefore been performed using the Cambridge helium-3 spin-echo facility (HeSE) 27,67,68 .…”
Section: Methodsmentioning
confidence: 99%
“…For example, on graphene, water has previously only been visualised when subsurface, due to its dynamic nature 61,62 . Compared with other techniques, He atom scattering has the advantage of being the most delicate surface-probing technique and is sensitive to H atoms in the top layer [63][64][65][66] . All measurements have therefore been performed using the Cambridge helium-3 spin-echo facility (HeSE) 27,67,68 .…”
Section: Methodsmentioning
confidence: 99%
“…Due to the large cross section of HAS to isolated adsorbates (including hydrogen as described in Section 3.5), the position and structure of hydrogen atoms and adsorbed water layers can be readily determined. [103][104][105] These include also the hydrogenation of a graphene surface 106 while H-positions are hard to determine with other methods (e.g., hydrogen is a weak scatterer for electrons) which also present a severe risk of damaging the H-layer. 107 In a study of highly proton-ordered water structures on oxygen pre-covered Ru(0001) it could be shown that the atomic oxygen and the oxygen from water form a (2 Â 2) surface reconstruction, which however, is broken by the hydrogen to give a (2 Â 4) surface reconstruction: while LEED measured a (2 Â 2), HAS measured a (2 Â 4) superstructure.…”
Section: Nanoscale Surface Topographymentioning
confidence: 99%
“…However, to make these fast diffusive motions accessible to microscopy studies, the process typically needs to be considerably slowed down. At the same time an intrinsic problem of scanning probe microscopy is that the probes inevitably induce perturbation to the fragile water structure, due to the excitation of tunnelling electrons and the tip-water interaction forces 10,14 .…”
mentioning
confidence: 99%